Cerebral Small Vessel Disease and Vertigo: A 10-Year Longitudinal Study on Geriatric Intervention and Outcomes - S. S. Subramanian (Medical Science: Trends and Innovations Vol. 1, 2025)
Cerebral small vessel disease (CSVD) represents a cluster of pathologies with a heterogeneous etiology and a pathomechanism affecting elements of the brain vascular system such as small arteries, capillaries, arterioles and venules. A Cluster of geriatric health issues which can lead to many neurodegenerative disorders including Parkinson’s disease, Alzheimer’s, and dementia. All these carry along with it a potential decline in quality of life, health care expenses; and a larger amount of disability. Vertigo was thought to be related to cardiovascular predictors. The two prime objectives of this study are to understand the pathogenesis of vertigo and evaluate the role of physiotherapy as a prophylactic therapeutics. An early identification of risk factors, along with treatment using due medication coupled with non-pharmacological treatment using physiotherapy were analyzed with evidence in a Ten-year follow-up of a subject with cerebral small vessel disease. The outcome of the research can be beneficial for geriatric subjects and to further the continuation of the findings of the research. This Research was carried out in longitudinal means from May 2011 to 2021 December with weekly twice physiotherapy sessions for 25-30 minutes at an exercise intensity of 60-70% of her maximal heart rate. Major functional problems faced by this research subject were neck pain and dizziness. Few researchers have linked dizziness among elders with CSVD leading to neurodegenerative disorders. Cerebral small vessel diseases, with risk arising from ageing, hypertension, and diabetes can better be medically diagnosed treated and duly followed up as it could lead to cognitive decline, dementia, falls physical dysfunctions resulting in physical and psychological challenges lowering an elderly subject’s quality of life. A holistic intervention, including regular physiotherapy, can to a larger extent, minimize the progression of CSVD as well as be beneficial by maximizing functional independence among the subjects. Further studies on other measurable variables such as NMRI, and specific parameters like gait, including other disciplines in the research are highly recommended.